2018
DOI: 10.18502/ijml.v5i4.155
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the status of iron and sclerostin in major Thalassemia Patients

Abstract: Background and Aims: Thalassemia is one the most prevalent genetic anemia in the world; homozygote patients usually suffer from severe disturbances. Osteopenia and osteoporosis are of various types of thalassemia complications which are increase in rate in patients with iron overload conditions. Sclerostin is a protein which enhances bone loss by inhibiting osteoblasts. The aim of this study was to measure sclerostin protein and its association with iron overload in major thalassemia patients. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…However, our results are not in line with the findings of Voskaridou [8] and Morabito et al [9] who reported a positive relationship in thalassaemia patients with osteoporosis. They are also different from Moinzadeh's study [39], which showed no relation between sclerostin serum levels and bone mineral density in osteoporotic TM patients. We presume that the difference could be due to the fact that in our study the patient group included not only osteoporotic, but also osteopenic and TDßT patients with normal BMD, thus respresenting a wider range of patient characteristics vs. the aforementioned studies which explored the same association in samples that were more homogeneous (restricted range).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, our results are not in line with the findings of Voskaridou [8] and Morabito et al [9] who reported a positive relationship in thalassaemia patients with osteoporosis. They are also different from Moinzadeh's study [39], which showed no relation between sclerostin serum levels and bone mineral density in osteoporotic TM patients. We presume that the difference could be due to the fact that in our study the patient group included not only osteoporotic, but also osteopenic and TDßT patients with normal BMD, thus respresenting a wider range of patient characteristics vs. the aforementioned studies which explored the same association in samples that were more homogeneous (restricted range).…”
Section: Discussioncontrasting
confidence: 99%
“…The negative association with pretransfusion haemoglobin was supported by very strong statistical evidence, however the 95%CI showed a rather large range of coefficients between À0.60 and À0.19, cautioning against any hasty conclusions. The uncertainty is coupled by the lack of related research specific to thalassaemia patients (at least to our knowledge), except for that by Moinzadeh et al [39] Yet, our finding can not be compared with the latter study because Moinzadeh et al did not explore the strength and direction of the relation between sclerostin and pretransfusion haemoglobin. The relationship of sclerostin with liver iron overload was significant, however not very strong.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations